Genetics of Resistance to Common Root Rot (Spot Blotch), Fusarium Crown Rot, and Sharp Eyespot in Wheat - Su, Jun; Zhao, Jiaojie; Zhao, Shuqing; Li, Mengyu; Pang, Shuyong; Kang, Zhensheng; Zhen, Wenchao; Chen, Shisheng; Chen, Feng; Wang, Xiaodong (Frontiers in Genetics, 2021)
Due to soil changes, high density planting, and the use of straw-returning methods, wheat common root rot (spot blotch), Fusarium crown rot (FCR), and sharp eyespot (sheath blight) have become severe threats to global wheat production. Only a few wheat genotypes show moderate resistance to these root and crown rot fungal diseases, and the genetic determinants of wheat resistance to these devastating diseases are poorly understood. This review summarizes recent results of genetic studies of wheat resistance to common root rot, Fusarium crown rot, and sharp eyespot. Wheat germplasm with relatively higher resistance are highlighted and genetic loci controlling the resistance to each disease are summarized.